1987
DOI: 10.1021/bi00398a064
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional crystals of enzyme-effector complexes: ribonucleotide reductase at 18-.ANG. resolution

Abstract: The B1 subunit of ribonucleotide reductase formed two-dimensional crystals when bound to and effector nucleotide linked to lipids in planar layers at the air/water interface. The effector lipid consisted of dATP coupled through the gamma-phosphoryl group and an epsilon-aminocaproyl linker to phosphatidylethanolamine. Two-dimensional crystals of B1 reductase, like those of antibodies and cholera toxin obtained previously, formed under physiologic conditions of pH and ionic strength, with no precipitant added to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Two-dimensional crystallization Two-dimensional crystallization of biological macromolecules using either charged (Darst et al, 1988(Darst et al, , 1989(Darst et al, , 1991Schultz et al, 1990a) or ligand exposing (Uzgiris and Kornberg, 1983;Ribi et al, 1987;Lebeau et al, 1990; Mosser et al, 1991) lipid layers has grown to become a powerful tool for electron microscopic studies of soluble proteins. These studies have shown that proteins are concentrated at the lipid -solvent interface upon interaction with the lipids and, in some cases, it has been shown that they are preferentially oriented (Schultz et al, 1990a (Darst et al, 1989(Darst et al, , 1990(Darst et al, , 1991.…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional crystallization Two-dimensional crystallization of biological macromolecules using either charged (Darst et al, 1988(Darst et al, , 1989(Darst et al, , 1991Schultz et al, 1990a) or ligand exposing (Uzgiris and Kornberg, 1983;Ribi et al, 1987;Lebeau et al, 1990; Mosser et al, 1991) lipid layers has grown to become a powerful tool for electron microscopic studies of soluble proteins. These studies have shown that proteins are concentrated at the lipid -solvent interface upon interaction with the lipids and, in some cases, it has been shown that they are preferentially oriented (Schultz et al, 1990a (Darst et al, 1989(Darst et al, , 1990(Darst et al, , 1991.…”
Section: Discussionmentioning
confidence: 99%
“…The length of the dimeric molecule is about 110 A and with a largest diameter of 75 A. We have compared our Rl structure with the object observed by image analysis of two-dimensional RI crystals [31]. Our suggestion is that the 110 A object they interpreted as an RI subunit more likely corresponds to one RI dimer.…”
Section: Resultsmentioning
confidence: 91%
“…Ribi et al synthesized functionalized lipid 4 containing dATP linked via L--dioleoylphosphatidylethanolamine (DOPE) 1 to obtain 2-D crystals of the B1 subunit of ribonucleotide reductase, an ATP-binding protein [18].…”
Section: Atp-lipidsmentioning
confidence: 99%
“…Electron micrographs of negatively stained crystals diffracted to 18 Å (Fig. (2)) and revealed the structure of the B1 subunit to be a dimer, consisting of a pair of cylindrical objects, each of 105-109 Å length and 31-34 Å in diameter [18].…”
Section: Atp-lipidsmentioning
confidence: 99%